(untitled) (Third Sector Social Economic Review, 2024)
The aim of this study is to examine the relationships between organizational justice perceptions, cynicism levels, and organizational commitment of employees in a central public sports organization. The relationship between these variables includes important parameters for increasing employee performance. The research group of this study, in which a quantitative research design was used, consists of 573 personnel working in the central organization of the Ministry of Youth and Sports and selected by random sampling method. The Organizational Justice Scale, the Organizational Cynicism Scale and the Organizational Commitment Scale were used as data collection tools. Descriptive, validity and reliability analyses, correlation analyses, hierarchical and multiple regression analyses were used in the analysis of the data. Regression and correlation analyses show that justice and cynicism affect organizational commitment. In the study, it was found that employees in environments where organizational justice is high exhibit higher organizational commitment, whereas commitment decreases in situations where organizational cynicism is high. As a result, it shows that ensuring organizational justice and reducing cynicism will support the long-term success and sustainability of organizations by increasing the commitment levels of employees. In addition to contributing to the organizational behavior literature, these results provide useful information about strategies for organizational commitment to increase the performance of employees in public institutions.